Pasting properties of high-amylose wheat in conventional and high-temperature Rapid Visco Analyzer: Molecular contribution of starch and gluten proteins. (October 2022) - Li, Hai-Teng; Kerr, Edward D.; Schulz, Benjamin L.; Gidley, Michael J.; Dhital, Sushil
Abstract: The popularity of high-amylose cultivars of main crops (e.g., high-amylose wheat, HAW) has been increasing because of their unique functional properties and enhanced nutritional values. In the current study, we employed the high-temperature Rapid Visco-Analyzer (HTRVA) to evaluate the performance of HAW flours and starches with an extensive range of amylose contents under high-temperature processing. The pasting parameters, total setback viscosity (TSV) and final viscosity (FV) from HTRVA, did not significantly correlate ( p > 0.05) with those from conventional RVA. The results indicate that conventional RVA could not robustly predict the pasting behaviours of HAW ingredients at high-temperature processing (partially due to different extent of starch disruption and leaching). The amylose content by iodine colorimetry method was not a good indicator of the cooling and retrogradation process of HAW flour and starch after high-temperature heating, with low R 2 values of the linear regression of TSV and FV on amylose content. However, TSV and FV of HAW flours as analysed by HTRVA negatively correlate ( p < 0.01) with wheat flour protein content, as well as with the abundance of glutenin (low molecular weight subunit, p < 0.05) as identified by a SWATH-MS (Sequential Window Acquisition of all Theoretical Mass Spectra) proteomics method. The protein attributes could contribute to restricting both swelling of granules during heating and the reassociation of starch polymers during cooling. Amylose (AM) and amylopectin (AP) fine structural features also regulate pasting behaviours. In particular, longer amylopectin outer chains promote peak viscosity, while larger amylose (whole) molecules have the opposite effect. This study presents new insights into the molecular basis for the pasting behaviours of HAW in conventional and high-temperature RVA. Graphical abstract: Image 1 Highlights: High-temperature RVA profiles were compared to conventional RVA profiles. High heating temperature reduced holding strength and final viscosity. Peak viscosity was increased by longer AP outer chains but reduced by larger AM. Total protein did not correlate with high temperature or conventional RVA parameters. Detailed glutenin profiles (e.g., LMW-GS) show correlations with pasting parameters.